Effect of Dual Modality of Presenting Information on Students' Achievement in a Science Unit - Shabana Hameed Syed (Indus Journal of Social Sciences, 2025)
This experimental study investigated the effect of dual modality of presenting information using both visual and auditory modes on students’ academic achievement in General Science at the pre 9th grade. Grounded in John Sweller’s Cognitive Load Theory, the study tested the hypothesis that students taught through dual modality would outperform those taught through a single modality. The sample comprised 36 female students from FG Public School (Girls), Lalazar, Rawalpindi, divided into experimental and control groups based on matched pretest scores. The experimental group received instruction through visual and auditory materials (e.g., diagrams, models, PowerPoint presentations), while the control group was taught using a lecture-based, single-mode approach. Data were collected through pretest and posttest instruments and analyzed using mean, standard deviation, and independent samples t-test at a 0.05 significance level. Results revealed a statistically significant difference in posttest achievement scores in favor of the experimental group (t = 3.138, p < 0.05), confirming that dual modality instruction enhances learning outcomes and retention. The findings support the modality effect proposed by Cognitive Load Theory, suggesting that integrating visual and auditory channels reduces cognitive overload and improves conceptual understanding. It is recommended that science teachers employ dual modality presentations to promote deeper learning and engagement among students.